PENERAPAN ASAS EQUALITY BEFORE THE LAW TERHADAP PELAKU TINDAK PIDANA KORUPSI DI WILAYAH HUKUM PENGADILAN TINDAK PIDANA KORUPSI PADA PENGADILAN NEGERI PEKANBARU - M. Fadhli Ariwibowo; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Adhering to the principle of equality before the law (the same position in law and government) should not be accused of corruption who received preferential treatment from one to the other actors. However, from the few cases that occurred in the Corruption Court On Court Pekanbaru. There are indications of neglect of the principle of equality before the law. Many things are exemplified not treated equally before the law in its application, whereas the same case with the other, as in granting the status of detention for suspects or defendants. The purpose of this thesis to To determine the application of the principle of equality before the law against the perpetrators of corruption in the jurisdiction of the District Court of Pekanbaru, to determine the resistance factor in the application of the principle of equality before the law against the perpetrators of corruption in the jurisdiction of the District Court of Pekanbaru and to know remedy in the application of the principle of equality before the law against the perpetrators of corruption in the jurisdiction of the District Court of Pekanbaru. This type of research will use juridical empirical sociological or juridical. Juridical sociological research or empirical research approach is to look at in terms of the fact that occur in the field. While research is a descriptive nature that aims to provide a clear picture of the problems examined.The results of this study concluded, Application of the principle of equality before the law against perpetrators of corruption in the jurisdiction of the District Court of Pekanbaru there are indications of violations of the principle of equality before the law. Assumption advocates, the media, law enforcement, and community still privilege against perpetrators of corruption in the Corruption Court in the District Court of Pekanbaru. Factors Barriers In principle Application Equality Before The Law Against Corruption Actors region Pekanbaru Law Court, namely the knowledge of law enforcement are not the same, a small law enforcement income, limited facilities and infrastructure factors, the lack of personnel judges, view Community Leaning Against Enforcement Process law, and the lack of effective oversight. Efforts to Address Constraints Application of Principle of Equality Before The Law Against Corruption Actors in Pekanbaru District Court Jurisdiction, which provides training to law enforcement, supervision tightened and involved parties to 3 (three), promote the welfare of Law Enforcement, Special Day Courts Act Corruption, Ad Hoc Judge Candidate Acceptance of Corruption, Corruption Session Recording, And Escort trial by police officers.Keywords: Equality Before The Law, Corruption.